HISTORY OF THE DEVELOPMENT OF CRAFTSMANSHIP IN THE KASHKADARYA REGION - Suyarova Feruza Sobir kizi (Western European Studies, 2025)
This article analyzes the historical development stages of handicrafts in the Kashkadarya region. The formation of such handicraft industries as pottery, blacksmithing, jewelry, textiles, and woodcarving in the region since ancient times is highlighted based on archaeological sources. It is revealed through scientific sources that in the Middle Ages, cities such as Shahrisabz and Karshi, located at the crossroads of caravan routes, were exported to domestic and foreign markets. The impact of technological innovations in the 19th and 20th centuries and the industrialization processes of the Soviet era on the development of handicrafts is analyzed. In the years after independence, the restoration of national handicrafts, the privileges and opportunities created by the state for craftsmen, participation in international exhibitions, and integration processes with tourism are considered on a separate scientific basis
Keywords: Kashkadarya; history of crafts; pottery; blacksmithing